Comparison of hip joint mechanical energetics in table tennis forehand and backhand drives - Thibault Marsan; Philippe Rouch; Patricia Thoreux; Rozenn Jacquet-Yquel; Christophe Sauret (Universidad de Granada, 2019)
Hip joints are highly involved in table tennis. Some authors found both pelvic angular velocity and hip joint torques are related to the racket velocity. Others have also demonstrated how some of the best players have higher ranges of motion of the lower-limb joints. Therefore, the mechanical work generated by the playing-side-hip can be seen as indicator of the playing intensity associated with different strokes. The aim of this study was to quantify the hip joint mechanical work and power during four classical strokes. Motion capture acquisitions were performed on two international players. A biplanar radiographic acquisition was also performed to personalize the biomechanical model. Hip joint velocity and torques were calculated on the dominant side, allowing mechanical power and work to be calculated between the end of backswing and the ball impact. The highest level of mechanical work from the hip joint was found for forehand drive against backspin and forehand topspin drive with pivot. A backhand drive required the lowest hip mechanical work, and the forehand drive against topspin was found to be intermediate. The lower work required from the backhand stroke makes it suitable as a waiting stroke.